Combined Scintigraphic and Radiographic Diagnosis of Bone and Joint Diseases Including Gamma Correction Interpretation - Bahk, Yong-Whee.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
In the fifth edition of this highly successful book, the author once again aims to equip the reader with up-to-date information that will facilitate accurate diagnosis of bone and joint diseases by means of combined use of scintigraphy and radiology. Two entirely new chapters have been added, one on the use of 18F-NaF PET/CT and the other on gamma correction scan diagnosis of bone trabecular microfracture and microcontusion as well as bone edema and hemorrhage. Further topics covered for the first time include enthesopathies, myositis, soft tissue diseases, cryptic bones, and differential diagnosis. Individual chapters have been updated and rearranged to reflect the latest advances in imaging diagnosis. As before, a vast number of state of the art gamma correction pinhole bone scans and corroborative conventional radiographs and CT, MRI, and/or ultrasound images are presented side by side. In this new edition, extension of the application of gamma correction to other imaging methods such as MRI and CT and the solution of the halation problem are necessarily addressed. This fifth edition of Combined Scintigraphic and Radiographic Diagnosis of Bone and Joint Diseases will be essential reading for practitioners and researchers in nuclear medicine, radiology, orthopedic surgery, pathology, anatomy, and imaging sciences at large.
Introduction and fundamentals of pinhole scintigraphy -- Dual-head planar pinhole scan, pinhole SPECT, and gamma correction pinhole scan of the bone -- Clinical applications -- Normal pinhole scintigraphic anatomy of bones and joints -- Normal variants and artifacts -- Infective and inflammatory diseases of the bone -- Noninfective osteitides -- Diseases of joints and soft-tissue infections -- Degenerative joint diseases -- Rheumatoid arthritis -- Seronegative spondyloarthropathies -- Other rheumatic osteoarthropathies and soft-tissue rheumatism syndromes -- Osteochondroses and related diseases -- Vascular bone disorders -- Metabolic bone diseases and drug-induced osteoporosis -- Traumatic, surgical, and sports injuries of the skeleton -- Malignant tumors of the bone -- Benign tumors and tumorous conditions of the bone -- Soft-tissue tumors and tumor-like conditions -- Otorhinological disorders -- PET-CT in bone and joint diseases -- A genetic consideration of skeletal disorders -- Gamma correction pinhole bone scan diagnosis -- Trabecular Microfracture and Micro contusion -- Appendix: Basic physics of pinhole scintigraphy.
Keywords: Medicine; Nuclear medicine; Oncology; Rheumatology; Orthopedics; Medicine & Public Health; Nuclear medicine; Oncology; Surgical Orthopedics; Rheumatology